Critical craft technology, globalization, and capitalism - Wilkinson-Weber, Clare M.; DeNicola, Alicia Ory (Bloomsbury Academic, 2016)
"From Oaxacan wood carvings to dessert kitchens in provincial France, Critical Craft presents thirteen ethnographies which examine what defines and makes 'craft' in a wide variety of practices from around the world.Challenging the conventional understanding of craft as a survival, a revival, or something that resists capitalism, the book turns instead to the designers, DIY enthusiasts, traditional artisans, and technical programmers who consider their labor to be craft, in order to comprehend how they make sense of it. The authors' ethnographic studies focus on the individuals and communities who claim a practice as their own, bypassing the question of craft survival to ask how and why activities termed craft are mobilized and reproduced. Moving beyond regional studies of heritage artisanship, the authors suggest that ideas of craft are by definition part of a larger cosmopolitan dialogue of power and identity. By paying careful attention to these sometimes conflicting voices, this collection shows that there is great flexibility in terms of which activities are labelled 'craft'. In fact, there are many related ideas of craft and these shape distinct engagements with materials, people, and the economy. Case studies from countries including Mexico, Nigeria, India, Taiwan, the Philippines, and France draw together evidence based on linguistics, microsociology, and participant observation to explore the shifting terrain on which those engaged in craft are operating. What emerges is a fascinating picture which shows how claims about craft are an integral part of contemporary global change"--Provided by publisher.